Evaluation of Durability of Clay Roofing Tiles - Cruz, C. (2012)
In Portugal, some cases of accelerated decay of clay roofing tiles localized in coastal zones can be quite worrying for industrial producers and final consumers. This degradation strongly conditions the roofing tiles durability and seems to arise from the exposition to the salt mist atmosphere at the seaside. An experimental study is being carried out to evaluate the performance of the clay roofing tiles subjected to sea environment, based on artificial accelerated weathering tests of exposition to salt mist. The study includes the roofing tiles characterization, the development of accelerated weathering tests, the evaluation of the weathering effect through observation and physical and chemical tests and also the comparison with roofing tiles that suffered natural weathering in coastal zones of Portugal. The objective is to obtain results which permit the identification of parameters - both of composition and manufacture - having a higher contribution to decay of the roofing tiles, to provide industry with relevant data to improve the manufacturing process. This paper presents tests and results obtained so far.